Mononuclear Ruthenium and Osmium Complexes with a Bicyclic Guanidinate Ligand: Synthesis and Catalytic Behavior in Olefin Isomerization Processes. Issue 35 (22nd September 2017) - Gámez‐Rivera, Sebastián A.; Francos, Javier; Borge, Javier; Cadierno, Victorio
Abstract : The preparation of the first mononuclear Ru II, Ru IV, and Os II complexes containing the anion of the bicyclic guanidine 1, 3, 4, 6, 7, 8‐hexahydro‐2 H ‐pyrimido[1, 2‐ a ]pyrimidine (Hhpp) as a chelating ligand, namely [RuXκ 2 ‐( N, N′ )‐hpp(η 6 ‐arene)] [arene = p ‐cymene, X = Cl (2a ), Br (2b ), I (2c ); arene = C6 Me6, X = Cl (7 )], [RuClκ 2 ‐( N, N′ )‐hpp(η 3 :η 3 ‐C10 H16 )] (9 ; C10 H16 = 2, 7‐dimethylocta‐2, 6‐diene‐1, 8‐diyl), and [OsClκ 2 ‐( N, N′ )‐hpp(η 6 ‐ p ‐cymene)] (11 ), is described. Compounds2a –c, 7, 9, and11 have been fully characterized by elemental analysis, HRMS, IR and NMR spectroscopy. In addition, the structure of2a has been unequivocally confirmed by single‐crystal X‐ray diffraction methods. The catalytic behavior of these metal guanidinate complexes in the base‐free redox isomerization of allylic alcohols is explored, with the ruthenium(IV) derivative9 showing the best performance (TOF up to 5940 h –1 ). All of the synthesized complexes have also proven to be active in the isomerization of the allylbenzene estragole into the industrially relevant 1‐propenylbenzene anethole, with a trans selectivity of up to 95 %. Abstract : New mononuclear Ru II, Ru IV, and Os II guanidinate complexes, derived from 1, 3, 4, 6, 7, 8‐hexahydro‐2 H ‐pyrimido[1, 2‐ a ]pyrimidine, have been synthesized and successfully employed as catalysts for the isomerization of allylic alcohols and estragole in both organic and aqueous media.